Peptide binding α1α2 domain of HLA-B27 contributes to the disease pathogenesis in transgenic mice - Khare, Sanjay; Hämmerling, Günter J. (Human immunology, 1999)
Human spondyloarthropathies are strongly associated with a major histocompatibility complex (MHC) class I allele, HLA-B27. HLA-B27 transgenic mice and rats demonstrate many features of these diseases further confirming the role of HLA-B27 in disease. Yet the exact role of this molecule in disease pathogenesis is not clearly understood. We have previously reported spontaneous arthritis and nail disease in HLA-B27 transgenic mice lacking β2-microglobulin (B27+β2mo). These observations alongwith binding studies of B27 derived peptides to HLA-B27 molecule itself led to two hypotheses: (i) HLA-B27 derived peptide as a source of autoantigen; and (ii) HLA-B27 functions as an antigen presenting molecule. In this report, we confirm spontaneous disease in transgenic mice expressing a hybrid B27 molecule with α1α2 domain of B27 and α3 domain of mouse H-2Kd. These mice developed spontaneous arthritis and nail disease when transferred from specific pathogen free barrier facility to the conventional area. Other control mice with MHC class I transgene (e.g., HLA-B7, HLA-Cw3, and H2-Dd) did not develop such disease. In a MHC reassembly assay, binding of similar peptides to both wild type and hybrid B27 molecules was observed. In addition, the hybrid B27 molecule lacks at least one of the 3 proposed peptides from the third hypervariable (HV3) region of HLA-B27. These data strongly suggest that HLA-B27 molecule is an antigen presenting molecule rather than a peptide donor in the disease pathogenesis.
Falsche Schreibweise von Günter Hämmerling
Gesehen am 16.02.2021